Effects of caffeine on neuromuscular function in a non‐fatigued state and during fatiguing exercise. Issue 4 (13th March 2020) - Mesquita, Ricardo N. O.; Cronin, Neil J.; Kyröläinen, Heikki; Hintikka, Jukka; Avela, Janne
Abstract : New Findings: What is the central question of the study? What are the effects of caffeine on neuromuscular function in a non‐fatigued state and during fatiguing exercise? What is the main finding and its importance? In a non‐fatigued state, caffeine decreased the duration of the silent period evoked by transcranial magnetic stimulation. Caffeine‐induced reduction of inhibitory mechanisms in the central nervous system before exercise was associated with an increased performance. Individuals who benefit from caffeine ingestion may experience lower perception of effort during exercise and an accelerated recovery of M‐wave amplitude postfatigue. This study elucidates the mechanisms of action of caffeine and demonstrates that inter‐individual variability of its effects on neuromuscular function is a fruitful area for further work. Abstract: Caffeine enhances exercise performance, but its mechanisms of action remain unclear. In this study, we investigated its effects on neuromuscular function in a non‐fatigued state and during fatiguing exercise. Eighteen men participated in this randomized, double‐blind, placebo‐controlled crossover trial. Baseline measures included plantarflexion force, drop jump, squat jump, voluntary activation of triceps surae muscle, soleus muscle contractile properties, M‐wave, α‐motoneuron excitability (H‐reflex), corticospinal excitability, short‐interval intracortical inhibition, intracortical facilitation, silent period evoked by transcranial magnetic stimulation (SP) and plasma potassium and caffeine concentrations. Immediately after baseline testing, participants ingested caffeine (6 mg·kg −1 ) or placebo. After a 1‐h rest, baseline measures were repeated, followed by a fatiguing stretch–shortening cycle exercise (sets of 40 bilateral rebound jumps on a sledge apparatus) until task failure. Neuromuscular testing was carried out throughout the fatigue protocol and afterwards. Caffeine enhanced drop jump height (by 4.2%) and decreased the SP (by 12.6%) in a non‐fatigued state. A caffeine‐related decrease in SP and short‐interval intracortical inhibition before the fatiguing activity was associated with an increased time to task failure. The participants who benefitted from an improved performance on the caffeine day reported a significantly lower sense of effort during exercise and had an accelerated postexercise recovery of M‐wave amplitude. Caffeine modulates inhibitory mechanisms of the CNS, recovery of M‐wave amplitude and perception of effort. This study lays the groundwork for future examinations of differences in caffeine‐induced neuromuscular changes between those who are deemed to benefit from caffeine ingestion and those who are not. Abstract :